2000
DOI: 10.1289/ehp.0010861
|View full text |Cite
|
Sign up to set email alerts
|

The p53 heterozygous knockout mouse as a model for chemical carcinogenesis in vascular tissue.

Abstract: Heterozygous p53 knockout mice were investigated as a potential model for vascular tumor carcinogenesis. Groups of 20 male mice were exposed by gavage for 6 months to the vascular carcinogen urethane at 1, 10, or 100 mg/kg body weight/day. Wild-type and heterozygous p53 knockout control groups were exposed by gavage to the vehicle alone. Another group of 20 male mice received d-limonene by gavage (d-limonene is noncarcinogenic in mice). The high dose of urethane caused early mortality in the majority of mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…To assess the potential merit of the three transgenic models in a research and testing program, we assembled available information on responses to chemical treatment in each model (Tables 1-3 (Carmichael et al 2000) +d (Spalding et al 1993) +ip (Mori et al 2000;Umemura et al 1999) Oxymetholone 434-07-1 2A Reasonable ±; +; NT; NT -; --g (Stoll et al 1999) +d (Stoll et al 1999 (Stoll et al 1999) NT (NTP 1990b)…”
Section: Merits Of the Modelsmentioning
confidence: 99%
“…To assess the potential merit of the three transgenic models in a research and testing program, we assembled available information on responses to chemical treatment in each model (Tables 1-3 (Carmichael et al 2000) +d (Spalding et al 1993) +ip (Mori et al 2000;Umemura et al 1999) Oxymetholone 434-07-1 2A Reasonable ±; +; NT; NT -; --g (Stoll et al 1999) +d (Stoll et al 1999 (Stoll et al 1999) NT (NTP 1990b)…”
Section: Merits Of the Modelsmentioning
confidence: 99%
“…In addition, accelerated tumor development with chemical exposure in p53 (+/-) mice has been reported with regard to lymphomas 51 , mesotheliomas 52 , skin tumors 53 , vascular tumors 14 , urinary bladder tumors 53 , and lung tumors 54 (representative photos of a sarcoma and a lymphoma are shown in Fig. 2, B and C).…”
Section: Target Cells Decide Sensitivity Of P53 (+/-) Micementioning
confidence: 81%
“…The same mouse model has also been widely utilized for functional analysis of the p53 gene in carcinogenesis studies. There have been several reports that p53 (+/-) mice are highly sensitive to genotoxic carcinogens, such as N-butyl-N- (4-hydroxybutyl)nitrosamine (BBN) targeting the urinary bladder 9 , N-ethyl-N-nitrosourea (ENU) inducing uterine endometrial stromal sarcomas 10 , N,Ndibutylnitrosamine (DBN) causing esophagus and urinary bladder tumors 11 , methyl-n-amylnitrosamine (MNAN) active in the esophagus 12 and tongue 13 and urethane inducing vascular tumors 14 . However, p53 (+/-) mice have not been shown to have increased susceptibility to induction of hepatocellular tumors by diethylnitrosamine (DEN) 15 or breast tumors by 7,12-dimethyl[a]benzanthracene (DMBA) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that whereas C57BL/6 mice are highly susceptible to hepatic vascular carcinogenesis, susceptibility to urethane-induced lung carcinogenesis is low (Carmichael et al, 2000). Thus, there are clear differences between rasH2 and p53 (+/−) mice in this regard.…”
Section: Introductionmentioning
confidence: 99%